2016
DOI: 10.1186/s12885-016-2880-2
|View full text |Cite
|
Sign up to set email alerts
|

A case series of intestinal adenomatous polyposis of unidentified etiology; a late effect of irradiation?

Abstract: BackgroundIn a large number of patients with multiple gastrointestinal adenomatous polyps, no causal germline mutation can be found. Non-genetic factors may contribute to the development of adenomatous polyps in these unexplained polyposis patients.In the development of gastrointestinal cancer, prior exposure to abdominal radiotherapy has been identified as such a factor, as it increases the gastrointestinal cancer risk in cancer survivors. A relationship of radiotherapy with intestinal polyposis, however, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…When considering more intensive CRC surveillance in HL survivors we must realise, however, that we do not know whether the pathogenesis of treatment-induced CRC in HL survivors is similar to that of CRC in the general population. As in the general population, most CRCs among HL survivors were adenocarcinomas and it appears that treatment-induced CRCs are preceded by adenomas as well ( Rigter et al , 2016 ; Rigter et al , 2017 ). Currently, most screening guidelines for HL survivors do not yet include CRC screening.…”
Section: Discussionmentioning
confidence: 81%
“…When considering more intensive CRC surveillance in HL survivors we must realise, however, that we do not know whether the pathogenesis of treatment-induced CRC in HL survivors is similar to that of CRC in the general population. As in the general population, most CRCs among HL survivors were adenocarcinomas and it appears that treatment-induced CRCs are preceded by adenomas as well ( Rigter et al , 2016 ; Rigter et al , 2017 ). Currently, most screening guidelines for HL survivors do not yet include CRC screening.…”
Section: Discussionmentioning
confidence: 81%
“…Advanced endoscopic techniques have the advantage of avoiding major abdominal surgery and bowel loss, especially in those with previous abdominal radiotherapy. The Dutch series 17 recommended surveillance colonoscopy of all HL patients no later than 40 years or 10 years after HL treatment, to be repeated every 5 years if negative, adjusting intervals based on findings. The 2018 Children's Oncology Group guidelines recommend colonoscopy for these survivors who received abdominopelvic radiotherapy either at age 30 or 5 years after radiotherapy, 11 then continue every 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…All patients received radiation and chemotherapy, and 2 were also found to have duodenal adenomas. 42 A multicenter US study identified 34 patients with therapy-associated polyposis, of which 22 (65%) did not have pathogenic variants on multigene panel testing. Of all, 10/34 (29%) only had single-gene testing, and 2/34 did not get tested.…”
Section: Therapy-associated Polyposismentioning
confidence: 99%
“…The third patient was treated for Hodgkin Lymphoma at age 20, and at age 62 underwent subtotal colectomy for 36 detected colonic adenomas. All patients received radiation and chemotherapy, and 2 were also found to have duodenal adenomas 42…”
Section: Clinical Phenotype Of Colorectal Neoplasia In Asccmentioning
confidence: 99%